Comparative evaluation of Panther Fusion and real-time PCR for detection of Burkholderia pseudomallei in spiked human blood. Issue 3 (21st March 2022) - Gassiep, Ian; Bauer, Michelle J.; Page, Melissa; Harris, Patrick N. A.; Norton, Robert
Abstract : Introduction. Melioidosis is an infection that most commonly presents with bacteraemia. Culture-based laboratory methods can result in a significant delay to organism identification. Molecular diagnostic techniques have a high sensitivity and rapid time to diagnosis. A decreased time to diagnosis is likely to improve patient outcomes. Aim. To compare the Panther Fusion automated molecular instrument to an in-house method for the detection of Burkholderia pseudomallei directly from spiked human whole-blood samples. Results. The in-house method detected 11/12 (92 %) samples with a B. pseudomallei concentration of 2.5–4.5×10 2 c.f.u. ml −1 . The Panther was less reliable, detecting only 8/14 (75 %) samples with a similar bacterial concentration. The Panther was able to detect 12/12 (100 %) spiked blood culture-positive samples. Conclusion. The direct detection of B. pseudomallei from patient blood on presentation to a healthcare facility will significantly decrease time to diagnosis. We describe an in-house real-time PCR method with the lowest reported limit of detection to date. Due to lower sensitivity, the Panther Fusion would be best used as a diagnostic method directly from a positive blood culture.